2007
DOI: 10.1074/jbc.m610719200
|View full text |Cite
|
Sign up to set email alerts
|

Sloppy Bypass of an Abasic Lesion Catalyzed by a Y-family DNA Polymerase

Abstract: DNA damage that eludes cellular repair pathways can arrest the replication machinery and stall the cell cycle. However, this damage can be bypassed by the Y-family DNA polymerases. Here, Dpo4, an archetypal Y-family member from the thermophilic Sulfolobus solfataricus, was used to extend our kinetic studies of the bypass of an abasic site, one of the most mutagenic and ubiquitous cellular lesions. A short oligonucleotide sequencing assay is developed to directly sequence DNA bypass products synthesized by Dpo4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 41 publications
2
39
0
Order By: Relevance
“…For example, it has been previously noted that there was inefficient misinsertion of dGTP opposite template T by Dpo4, and that the bases of either the incoming nucleotide or the 3′ nucleotide of the primer strand were disordered in the electron density maps, indicating conformational heterogeneity (Vaisman et al, 2005). The array of possibilities in the accommodation of an abasic site within the Dpo4 active site includes base deletion and addition frameshift structures (Ling et al, 2004a); this correlates with a ∼200-fold slower insertion and extension opposite an abasic site compared with an unmodified template (Fiala et al, 2007) and various mutagenic events observed in the fully extended products (Fiala and Suo, 2007). Conformational heterogeneity of lesions and their pairing partners, involving either a 3′-primer terminus or an incoming dNTP (Yang and Woodgate, 2007), creates a challenge to achieving a reaction-ready alignment of the spacious active site, thereby suggestive of a dynamic fidelity-check screening mechanism in Y-family polymerases.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been previously noted that there was inefficient misinsertion of dGTP opposite template T by Dpo4, and that the bases of either the incoming nucleotide or the 3′ nucleotide of the primer strand were disordered in the electron density maps, indicating conformational heterogeneity (Vaisman et al, 2005). The array of possibilities in the accommodation of an abasic site within the Dpo4 active site includes base deletion and addition frameshift structures (Ling et al, 2004a); this correlates with a ∼200-fold slower insertion and extension opposite an abasic site compared with an unmodified template (Fiala et al, 2007) and various mutagenic events observed in the fully extended products (Fiala and Suo, 2007). Conformational heterogeneity of lesions and their pairing partners, involving either a 3′-primer terminus or an incoming dNTP (Yang and Woodgate, 2007), creates a challenge to achieving a reaction-ready alignment of the spacious active site, thereby suggestive of a dynamic fidelity-check screening mechanism in Y-family polymerases.…”
Section: Discussionmentioning
confidence: 99%
“…Running Start Assay-The running start assay was performed as previously described (17,18,26). Briefly, a preincubated solution of 5Ј-32 P-labeled DNA (100 nM) and Dpo4 (100 nM) in buffer R was rapidly mixed with a solution containing all four dNTPs (200 M each) at 37°C via a rapid chemical-quench flow apparatus (KinTek).…”
Section: Methodsmentioning
confidence: 99%
“…103 This novel methodology was used to confirm the relative frequencies of insertion of dATP versus insertion of dCTP via the lesion loop-out mechanism predicted from the kinetic efficiencies of each pathway and to provide information about more rare mutation events both opposite and downstream from the lesion. 103 The development of “next-generation sequencing” allows for a high-throughput alternative to the original SOSA method and has been used to assess the mutagenic profiles of several carboxymethylated DNA lesions in E. coli .…”
Section: Pre-steady-state Kinetic and Sequencing Studies Of The Mechamentioning
confidence: 99%
“…103 This novel methodology was used to confirm the relative frequencies of insertion of dATP versus insertion of dCTP via the lesion loop-out mechanism predicted from the kinetic efficiencies of each pathway and to provide information about more rare mutation events both opposite and downstream from the lesion. 103 The development of “next-generation sequencing” allows for a high-throughput alternative to the original SOSA method and has been used to assess the mutagenic profiles of several carboxymethylated DNA lesions in E. coli . 104 In a recent publication, novel software (Next-Generation Position Base Counter, available for download at ) was developed to allow for efficient analysis of millions of DNA sequences yielded from the next-generation sequencing-based high-throughput version of the SOSA technique (HT-SOSA).…”
Section: Pre-steady-state Kinetic and Sequencing Studies Of The Mechamentioning
confidence: 99%